High expression of HLA-DQA1 predicts poor outcome in patients with esophageal squamous cell carcinoma in Northern China. Issue 8 (February 2019) - Shen, Fang-Fang; Pan, Ying; Li, Jing-Zhong; Zhao, Fang; Yang, Hai-Jun; Li, Jun-Kuo; Gao, Zhao-Wei; Su, Jing-Fen; Duan, Li-Juan; Lun, Shu-Min; Zhang, Peng; Tian, Lin-Qiang; et al.
Abstract: Background: Our previous studies demonstrate that the major histocompatibility complex (MHC) is associated with the progression of esophageal squamous cell carcinoma (ESCC). HLA-DQA1, which belongs to the MHC Class II family, may be a potential biomarker in ESCC progression. However, the association between HLA-DQA1 and ESCC in high-incidence area of northern China has not been well characterized. The purpose of this study is to investigate the relationship of HLA-DQA1 expression with the progression and prognosis of ESCC. Methods: We analyzed the expression profiles of HLA-DQA1 in esophageal cancer (EC) samples in the TCGA database and validated HLA-DQA1 expression by immunohistochemistry, western blotting, and quantitative reverse-transcription polymerase chain reaction in matched EC and normal tissues, respectively. The correlation between HLA-DQA1 expression and clinicopathologic characteristics of ESCC was further analyzed. Result: Immunohistochemical analysis indicated that the expression level of HLA-DQA1 in ESCC tissues was significantly higher than the matched normal tissues ( P  < .001). HLA-DQA1 mRNA and protein expression were significantly higher in ESCC tissues compared to the matched normal tissues. Patients with family history negative or with tumor sizes >4 cm were associated with higher HLA-DQA1 expression levels. A prognostic significance of HLA-DQA1 was also found by the Log-rank method, in which high expression of HLA-DQA1 was correlated with a shorter overall survival time. The receiver operating characteristic (ROC) curve analysis yielded the area under the ROC curve value of 0.693. Univariate and multivariate analyses also suggest that high expression of HLA-DQA1 is a potential indicator for poor prognosis of ESCC. Conclusions: Our results demonstrate that HLA-DQA1 plays an important role in ESCC progression and may be a biomarker for ESCC diagnosis and prognosis, as well as a potential target for the treatment of patients with ESCC.